Regulation of cation currents through the plasma membrane of root cells of higher plants under the influence of copper, iron and titanium oxide nanoparticles - Hryvusevich, Palina V.; Artsisheuskaya, Veranika Ya.; Mysleika, Marharyta A.; Sokolik, Anatoliy I.; Pshybytko, Natallia L.; Smolich, Ihar I.; Demidchik, Vadim V. (Experimental Biology and Biotechnology, 2026)
The development and use of environmentally friendly and highly effective forms of fertilisers based on nanoparticles are important subjects in modern plant biology. In this area one of the key problems is the assessment of the impact of metal-containing nanoparticles, such as copper, iron and titanium oxides, on the functioning of membrane ion transport systems in root cells of higher plants. In the present work using the local potential clamp method (patchclamp) the effect of CuO, Fe3O4 and TiO2 nanoparticles on activities of outward-rectifying K+ channels and inward-rectifying Ca2+ channels of the plasma membrane of Arabidopsis thaliana (L.) Heynh. root cells were investigated in detail. It was demonstrated that CuO and TiO2 nanoparticles at a concentration of 300 mg/L inhibited outward K+ currents and inward Ca2+ currents across the plasma membrane, when the time exposure was up to 15 min. With an increase in the exposure time for CuO nanoparticles to 30 min, activation of K+ and Ca2+ currents was recorded, which was probably associated with redox-dependent stimulation of the cation channels. Fe3O4 nanoparticles did not cause changes in the pattern of ionic currents through the plasma membrane of root cells. There were also no effects, when using the corresponding macroparticles (bulk form; more than 1 μm) instead of nanoparticles. Fe3O4 nanoparticles, which do not have membranotropic effects, were tested as growth stimulants in special small-volume cultivation systems. It was shown that these nanoparticles, starting from their level in the medium of 300 mg/L, stimulated growth of A. thaliana. This fact indicates a high potential for their use as nanofertilisers. The obtained data reveal new patterns of the effect of nanomaterials on the ion-transport mechanisms of plant cell membranes, demonstrating significant membranotropic effects of CuO and TiO2 nanoparticles and relative inertness with respect to cell membranes of Fe3O4 nanoparticles.
Keywords: patch-clamp; Arabidopsis thaliana (L.) Heynh.; potassium channels; calcium channels; metal oxide nanoparticles; nanofertilisers